Solution-focused brief counseling to improve student’s social-emotional skills and psychological well-being - Naraswari, Ida Ayu Made Diah; Dantes, Nyoman; Suarni, Ni Ketut; Gading, I Ketut; Suranata, Kadek (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
Indonesian education has transformed along with the current situations. Through the implementation of guidance and counseling service, schools should facilitate students to develop various non-cognitive skills and ensure that student’s mental health can well-achieved. This study aims to examine the effectiveness of solution-focused brief counseling (SFBC) to improve student’s social-emotional skills and psychological well-being. Following the experimental pretest-posttest control group design procedure, 64 junior high school students were involved as research subjects. Instruments in this study used 71-item social-emotional skills questionnaire and 42-item psychological well-being scale. The experimental group will be following 9 sessions of counseling, while the control group will not involve in any intervention. Data analysis in this study was carried out using one-way ANOVA and MANOVA. Results of this study found that (1) SFBC is effective to improving student’s social-emotional skills, (2) SFBC is effective to improving student’s psychological well-being, and (3) SFBC is simultaneously effective to improve student’s social-emotional skills and psychological well-being. The findings of this study have implications for the use of SFBC model as an intervention method to improve student’s non-cognitive skills and psychological well-being.